Studying Islam and Its Adherents in Australian Universities - Ali, Jan A. (Jurnal Pendidikan Islam, 2021)
Islamic Studies is a relatively new, yet growing phenomenon in Australian universities. With an increased focus on Islam and Muslim in the age of War on Terror and with Australian Muslim population fast increasing, Islamic Studies is an important intellectual tool to better understand, Islam and Muslims and many challenges facing them. This paper is an investigation of the recent trends and developments in Islamic Studies as an academic discipline in Australian universities. This is an important intellectual task because Islamic Studies continues to play a significant role in Australian academia. The data were collected from literature review and are analysed descriptively. The findings of the study show that the intellectual tools developed in Islamic Studies can be deployed to build relationship between fragmented Muslim communities and between Muslims and non-Muslims particularly in multicultural Australia. Islamic Studies draws on a variety of fields making it a crossdiscipline. As such, it offer a rich and analytic investigation of world’s second largest religion and its multiple expressions. Australian universities offer Islamic studies ranging from undergraduate to postgraduate program. The topic studied include Islamic philosophy, jurisprudence, education, history, and Arabic.